A commentary on selected speeches of Isaios - Isaeus, approximately 420 B.C.-approximately 350 B.C (Brill, 2013)
In 'A commentary on selected speeches of Isaios', Brenda Griffith-Williams offers a fresh insight, accessible to non-Greek readers, into four disputed inheritance cases from the Athenian courts in the 4th century B.C. The only comprehensive English language commentary on Isaios (Wyse, 1904) reflects a negative view of the Athenian legal system as one in which the judges, who had no legal training, could be easily outwitted by an unscrupulous speechwriter with no regard for the truth. By addressing the complex interplay of factual, legal, and rhetorical issues in the selected speeches, Brenda Griffith-Williams identifies the strengths and weaknesses of each speaker's case and presents a more balanced assessment of Isaios's work.
Revision of the author's doctoral thesis, University of London - 2009.
Keywords: Isaeus, -- approximately 420 B.C.-approximately 350 B.C. -- Translations into English.; Isaeus, -- approximately 420 B.C.-approximately 350 B.C.; Inheritance and succession (Greek law); Inheritance and succession -- Greece -- Athens -- History -- To 1500.; Forensic orations -- Greece -- Athens -- History -- To 1500.; Speeches, addresses, etc., Greek -- Translations into English.; Successions et héritages (Droit grec); LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; Forensic orations; Inheritance and succession; Speeches, addresses, etc., Greek; Greece -- Athens; To 1500; History; Translations